Improving feeding efficiencies of black soldier fly larvae, Hermetia illucens (L., 1758) (Diptera : Stratiomyidae : Hermetiinae) through manipulation of feeding conditions for industrial mass rearing - Brits, Devon (Stellenbosch : Stellenbosch University, 2017)
Thesis (MScConsEcol)--Stellenbosch University, 2017.